2019
DOI: 10.1177/2192568219831963
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Coccygectomy Using the “Z” Plasty Technique of Wound Closure

Abstract: Study Design:Technical note.Objectives:Coccygectomy for chronic coccydynia has a high rate of successful clinical outcome. However, the procedure is associated with increased incidence of wound dehiscence and surgical site infection. The main objective was to evaluate the clinical outcomes of coccygectomy using the Z plasty technique of wound closure.Methods:Patients with chronic coccydynia refractory to conservative treatment underwent coccygectomy followed by Z plasty technique of wound closure between Janua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 26 publications
0
22
0
Order By: Relevance
“…43 A recent modification described by Kulkarni et al adds a Z-plasty to the incision in order to reduce the tension and centrifugal forces acting on the incision, and therefore reducing the incidence of wound related complications. 41 The dissection proceeds with a sacro-coccygeal discectomy from cranial to caudal direction as described by Key to avoid an injury to the rectum, especially in anteverted coccyx; however, some surgeons have described the release of ano-coccygeal ligament first followed by elevating the distal end of the coccyx. 13,41 The amputation can be done at or slightly proximal to the sacrococcygeal junction.…”
Section: Treatmentmentioning
confidence: 99%
See 2 more Smart Citations
“…43 A recent modification described by Kulkarni et al adds a Z-plasty to the incision in order to reduce the tension and centrifugal forces acting on the incision, and therefore reducing the incidence of wound related complications. 41 The dissection proceeds with a sacro-coccygeal discectomy from cranial to caudal direction as described by Key to avoid an injury to the rectum, especially in anteverted coccyx; however, some surgeons have described the release of ano-coccygeal ligament first followed by elevating the distal end of the coccyx. 13,41 The amputation can be done at or slightly proximal to the sacrococcygeal junction.…”
Section: Treatmentmentioning
confidence: 99%
“…41 The dissection proceeds with a sacro-coccygeal discectomy from cranial to caudal direction as described by Key to avoid an injury to the rectum, especially in anteverted coccyx; however, some surgeons have described the release of ano-coccygeal ligament first followed by elevating the distal end of the coccyx. 13,41 The amputation can be done at or slightly proximal to the sacrococcygeal junction. Sacro-coccygeal junction can be identified by the cornuate articulation posteriorly.…”
Section: Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, meticulous apposition of the flaps without tension is achieved using interrupted subcutaneous 2-0 Vicryl stitches. 13 Many studies have confirmed the effectiveness of coccygectomy in accomplishing pain control in most cases. [14][15][16][17][18][19][20] However, pain-free rates postcoccygectomy may be influenced by the specific etiology causing coccydynia.…”
Section: Discussionmentioning
confidence: 97%
“… 8 Recently, a “Z” plasty technique was used in wound closure to the distal end of the vertical incision to reduce wound dehiscence and infection rates. 13 In this technique, considering the primary vertical incision as the central limb of the “Z,” the incision is extended in opposite directions at an angle of 60°. Then, the flaps are raised such that the surgical wound looks like a parallelogram.…”
Section: Discussionmentioning
confidence: 99%